Reproducing Leaders through Mentoring - Payne, Ian (Journal of Christian education, 2009)
This article proposes that theological educational institutions can play a significant part in producing the leaders the Church needs by mentoring their students more effectively. Mentoring new leaders is a necessary and exciting task for theological and developmental reasons, and theological educators must know and use the power of mentoring, as an essential element of transformative education, if their students are to be transformed. A mentoring model is preferred over ‘an academically-distant superior lecturer’ or an unmodified ‘guru-shishya’ model of relationship in order to give young leaders the support, challenge and mutuality in discipleship that they and the Church need.